2019
DOI: 10.1002/mgg3.940
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of family screening in hypertrophic cardiomyopathy and an online video intervention to facilitate family communication

Abstract: BackgroundIndividuals with hypertrophic cardiomyopathy (HCM), even when asymptomatic, are at‐risk for sudden cardiac death and stroke from arrhythmias, making it imperative to identify individuals affected by this familial disorder. Consensus guidelines recommend that first‐degree relatives (FDRs) of a person with HCM undergo serial cardiovascular evaluations.MethodsWe determined the uptake of family screening in patients with HCM and developed an online video intervention to facilitate family communication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…While family communication and risk disclosure are well‐studied, further understanding is also needed for the second step of the process: the relatives’ decisions around seeking cascade testing. Studies related to disclosure of genetic risk showed that probands generally did inform at least some relatives, but the uptake of testing did not necessarily reflect the number of people who were informed (Harris et al., 2019). This suggests that the factors impacting relatives’ understanding and decisions also play an important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While family communication and risk disclosure are well‐studied, further understanding is also needed for the second step of the process: the relatives’ decisions around seeking cascade testing. Studies related to disclosure of genetic risk showed that probands generally did inform at least some relatives, but the uptake of testing did not necessarily reflect the number of people who were informed (Harris et al., 2019). This suggests that the factors impacting relatives’ understanding and decisions also play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ensuring at‐risk relatives are notified, direct contact is also potentially more cost‐effective (Newson & Humphries, 2005). Direct contact methods have been used in the US and European countries for studies related to the family communication of genetic risk, and patient perspectives on direct contact found that the response was generally positive, with many of the participants feeling that direct contact was acceptable (Aktan‐Collan et al., 2007; Hammer et al., 2000; Harris et al., 2019; Kerzin‐Storrar et al., 2002; van Maarle et al., 2001; Marteau et al., 2004; Schwiter et al., 2020; Wilcke et al., 2000; Wright et al., 2002). However, the ethical considerations related to direct contact imply that it is not a ‘one size fits all’ approach; the severity and penetrance of a condition, availability of intervention, and balance of potential harm are all taken into consideration (Offit et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In studies describing cascade screening, often the participation of relatives is limited. [343][344][345][346][347][348] This implies that many persons carrying pathogenic variants remain undiagnosed and are at continued risk of sudden death. Increasingly, geneticists and other stakeholders plea for an active approach to cascade testing for conditions where interventions are available.…”
Section: Investigation Of the Family: Cause Identified-cascade Testing Clinical And Genetic Investigationsmentioning
confidence: 99%
“…In studies describing cascade screening, often the participation of relatives is limited 343–348 . This implies that many persons carrying pathogenic variants remain undiagnosed and are at continued risk of sudden death.…”
Section: Investigation Of the Familymentioning
confidence: 99%